Effects of catecholamines on secretion of adrenocorticotrophic hormone (ACTH) in man. Issue 9 (September 1987) - Al-Damluji, S; Rees, L H
Abstract : The hypothalamus receives a rich supply of adrenergic and noradrenergic nerve fibres from the brain stem, terminating in many hypothalamic regions, including the paraventricular nucleus, which is the site of the cell bodies of corticotrophin releasing factor (CRF) neurones in man. Experimental evidence has shown that an alpha 1 adrenoceptor mechanism stimulates adrenocorticotrophic hormone (ACTH) secretion in man. The site of action of this mechanism seems to be within the blood brain barrier, presumably modulating the secretion of the CRF complex. This mechanism is important in the control of ACTH secretion in some physiological conditions in healthy subjects.